Exploring community stakeholder perspectives of partnership development in community-engaged undergraduate Global Health Education in the UK: a qualitative study - Shyam Sundar Budhathoki; Helen Ward; Dorota Chapko; Christine Pettitt; Keitumetse-Kabelo Murray (BMJ Open)
Objectives Traditionally, patients have had passive roles in medical education; however, there have been increasing efforts to partner with communities to create authentic representation of laypeople in medical education. Communities’ perspectives of these initiatives have rarely been reported in the literature. This study explores the perspectives of members of community-based organisations (CBOs) who were partnered with a community engagement programme for intercalating medical students at Imperial College London.Design A qualitative study using semistructured interviews was conducted, employing reflexive thematic analysis.Setting London, UK.Participants A total of five participants (one member from five CBOs who agreed to participate) were interviewed for this study. The selection criterion was direct involvement in the community engagement programme.Results Three key themes were identified aligning with the core principles of co-production: building partnership, reciprocity in partnership and maintenance of relationship. Partnership development was influenced by the CBOs’ perception of students which caused power differentials in the development of learning plans. Reciprocity refers to a multidirectional benefit pathway resulting from the community involvement programme, which had short-term and anticipated long-term effects. Relationships built were maintained via a service evaluation report, and participants discussed how attitudes of academic institutions towards collaboration influence communities’ ability to participate in medical education.Conclusions The perspectives of CBOs reported in this study demonstrate that factors important to partnership development in community-engaged medical education are consistent with the key principles of co-production. Supported by literature, the findings emphasise that community involvement can be linked to social accountability and sustainable health practice. Provided that the possible risks/challenges are appropriately identified and mitigated to facilitate co-productive partnerships between stakeholders, the involvement of CBOs in medical education has the potential to provide benefits for communities, students and educational institutions.